2017
DOI: 10.3389/fneur.2017.00498
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Depression: Impact of Lesion Location and Methodological Limitations—A Topical Review

Abstract: Post-stroke depression (PSD) affects approximately one-third of all stroke patients. It hinders rehabilitation and is associated with worse functional outcome and increased mortality. Since the identification of PSD is a significant clinical problem, clinicians and researchers have tried to identify predictors that indicate patients at risk of developing PSD. This also includes the research question whether there is an association between PSD and stroke lesion characteristics, e.g., lesion size and lesion loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
6
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 77 publications
11
69
6
4
Order By: Relevance
“…Also, lesion location was not predictive for depression in our cohort, which is in line with several previous results [ 9 , 10 ]. However a longstanding debate on the role of this factor is still open [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, lesion location was not predictive for depression in our cohort, which is in line with several previous results [ 9 , 10 ]. However a longstanding debate on the role of this factor is still open [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 More recent studies using voxel-based lesion symptom mapping, which normalizes and coregistered brain imaging data into a standard template and therefore represents a more quantitative approach to study lesion locations, have also reported conflicting findings. [8][9][10] This inconsistency among single studies is reflected in systematic reviews 3,11,12 and metaanalyses, 13,14 which have been unable to reveal any associations between lesion locations and…”
Section: Resultsmentioning
confidence: 99%
“…One of the models that have been proposed is that subcortical strokes like those in the basal ganglia, and strokes in the frontal lobes can result in disrupted serotoninergic and norepinephrinergic pathways that can be associated with poststroke depression [21]. The belief is that strokes that affected the amine-containing axons between the brainstem and specifically the left cerebral cortex would result in decreased production of serotonin (5-HT) and norepinephrine [22]. A reduction of these neurotransmitters in the frontal and temporal lobe limbic structures, and in the basal ganglia could result in difficulty with mood regulation [19].…”
Section: Localization Of Poststroke Depressionmentioning
confidence: 99%